Beneficial Role of Rosuvastatin in Blood–Brain Barrier Damage Following Experimental Ischemic Stroke - Lu, Dan; Mai, Hong-Cheng; Liang, Yu-Bin; Xu, Bing-Dong; Xu, An-Ding; Zhang, Yu-Sheng (Frontiers in Pharmacology, 2018)
Hemorrhage transformation is the most challenging preventable complication in thrombolytic therapy and is related to recombinant tissue plasminogen activator (rt-PA)-induced blood-brain barrier (BBB) damage. Intraperitoneal injections of normal or high doses of rosuvastatin were administered to Balb/c mice 20 min prior to middle cerebral artery occlusion (MCAO) surgery for 3 h followed by reperfusion with rt-PA thrombolytic therapy and cerebral blood ﬂow monitoring to investigate whether a high or normal dose of rosuvastatin reduces BBB damage after brain ischemia and rt-PA reperfusion,. The integrity of the BBB was ameliorated by normal and high doses of rosuvastatin as determined from Evans blue staining, ultrastructure assessments and immunochemistry at 24 h after reperfusion. The levels of tight junction (TJ) proteins were preserved, potentially by targeting platelet-derived growth factor receptor α (PDGFR-α) and low-density lipoprotein receptor-related protein 1 (LRP1) to inhibit the expression of matrix metalloproteinase proteins (MMPs) by reducing the levels of phosphorylated c-jun-N-terminal kinase (pJNK), phosphorylated mitogen-activated protein kinase (MAPK) p38 (pP38) and increasing the levels of phosphorylated extracellular regulated protein kinases (pERK), and tissue inhibitor of metalloproteinases (TIMPs), as inferred from Western blotting and molecular docking analyses. In summary, rosuvastatin reduced rt-PA therapy-associated BBB permeability by PDGFR-α- and LRP1-associated MAPK pathways to reduce the mortality of mice, and a normal dose of rosuvastatin exerted greater preventative effects on reducing BBB damage than did a high dose in the time window of thrombolytic therapy.